2004
DOI: 10.1289/ehp.7197
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic on the Hands of Children after Playing in Playgrounds

Abstract: Increasing concerns over the use of wood treated with chromated copper arsenate (CCA) in playground structures arise from potential exposure to arsenic of children playing in these playgrounds. Limited data from previous studies analyzing arsenic levels in sand samples collected from CCA playgrounds are inconsistent and cannot be directly translated to the amount of children’s exposure to arsenic. The objective of this study was to determine the quantitative amounts of arsenic on the hands of children in conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
84
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(88 citation statements)
references
References 20 publications
1
84
1
2
Order By: Relevance
“…However, application of phosphorous-rich fertilizers to these soils, many of which are overlain by lawns, could potentially lead to the mobilization of the added As in Norfolk soils (e.g., Peryea and Kammereck 1997). Furthermore, a recent study demonstrated that children playing in playgrounds with chromated copper arsenate treated wooden playground structures or with sand that has come in contact with such structures, acquire more soluble As on their hands compared to children not exposed to such structures or the associated sand (Kwon et al 2004). Moreover, children that live near open-pit coal mines more frequently complain of respiratory distress to family physicians than children living more distal to such operations (Howel et al 2001;Moffatt and Pless-Mulloli 2003).…”
Section: Arsenic (Mg/kg)mentioning
confidence: 99%
“…However, application of phosphorous-rich fertilizers to these soils, many of which are overlain by lawns, could potentially lead to the mobilization of the added As in Norfolk soils (e.g., Peryea and Kammereck 1997). Furthermore, a recent study demonstrated that children playing in playgrounds with chromated copper arsenate treated wooden playground structures or with sand that has come in contact with such structures, acquire more soluble As on their hands compared to children not exposed to such structures or the associated sand (Kwon et al 2004). Moreover, children that live near open-pit coal mines more frequently complain of respiratory distress to family physicians than children living more distal to such operations (Howel et al 2001;Moffatt and Pless-Mulloli 2003).…”
Section: Arsenic (Mg/kg)mentioning
confidence: 99%
“…The main exposure route of human beings to As is by accidental soil ingestion by children, who frequently have contact with soil in regions with high levels of the element (Cohen et al, 1998;Rodriguez et al, 1999;Hemond & Solo-Gabriele, 2004;Kwon et al, 2004). Exposure to As by dermal absorption and inhalation is considered negligible compared to ingestion (Kwon et al, 2004;De Miguel et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to As by dermal absorption and inhalation is considered negligible compared to ingestion (Kwon et al, 2004;De Miguel et al, 2007). Considering the importance of this human exposure pathway (soil ingestion), and the restrictions associated to using human beings as test subjects, two types of tests (bioavailability and bioaccessibility) are used nowadays for the purpose of estimating exposure doses, an important step in human health risk assessment.…”
Section: Introductionmentioning
confidence: 99%
“…The filter residue from the hand-wash water probably contained at least some wood particles with much higher arsenic concentrations and lower densities than the playground sand. Hemond and Solo-Gabriele (2004) reviewed studies in which (typically adult) human hands were used to deliberately wipe CCA-treated lumber and reported much higher arsenic residues on hands than found by Kwon et al (2004). One obvious potential explanation is that the arsenic concentration in material dislodged from CCA-treated wood (Nico et al 2004) can easily be 1,000-fold higher than the 2-3 ppm found by Kwon et al in playground sand.…”
mentioning
confidence: 96%
“…Hence any reassuring conclusion based on this work is a reflection of the assumed rate at which hand residues are orally harvested and not of the reported measurements. Kwon et al (2004) further concluded that Most of the arsenic on children's hands is water soluble and is readily washed off with water. We recommend that children wash their hands after playing to reduce their potential exposure to arsenic.…”
mentioning
confidence: 99%